Data Analysis Time Series For Forecasting The Greenhouse Effect - Umami, Fauzah; Cipta, Hendra; Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2019)
The greenhouse effect is a term used to describe the earth having a greenhouse effect where the sun's heat is trapped by the earth's atmosphere. This study aims to model the greenhouse effect and then predict the greenhouse effect in the coming period using the Autoregressive Integrated Moving Average (ARIMA) method. In this case, time series analysis and reference data for 31 months are used, from the period January 2017 - July 2019, the results of the ARIMA model that are suitable for forecasting the greenhouse effect are ARIMA (4.2.0) with Mean Square Error (MSE) of 161885